2021
DOI: 10.3390/rs13061190
|View full text |Cite
|
Sign up to set email alerts
|

Planetary Wave Spectrum in the Stratosphere–Mesosphere during Sudden Stratospheric Warming 2018

Abstract: The planetary wave activity in the stratosphere–mesosphere during the Arctic major Sudden Stratospheric Warming (SSW) in February 2018 is discussed on the basis of microwave radiometer (MWR) measurements of carbon monoxide (CO) above Kharkiv, Ukraine (50.0° N, 36.3° E) and the Aura Microwave Limb Sounder (MLS) measurements of CO, temperature and geopotential heights. From the MLS data, eastward and westward migrations of wave 1/wave 2 spectral components were differentiated, to which less attention was paid in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…It was shown that the altitude dependence is not only in the amplitudes of wave 1 and wave 2 [23], but also in the direction of wave migration. Wave 1 migrates westward (eastward) in the stratosphere (mesosphere) in the pre-warming period and the dominant westward wave 1 exists in the post-warming mesosphere [5]. In the events SSW 2018 and SSW 2019, a similar equatorward shift of the maximum wave amplitude at 10 hPa was found: 60-80°N (wave 1), 50-70°N (wave 2), and 50-60°N (wave 3) [24].…”
Section: Introductionmentioning
confidence: 68%
See 4 more Smart Citations
“…It was shown that the altitude dependence is not only in the amplitudes of wave 1 and wave 2 [23], but also in the direction of wave migration. Wave 1 migrates westward (eastward) in the stratosphere (mesosphere) in the pre-warming period and the dominant westward wave 1 exists in the post-warming mesosphere [5]. In the events SSW 2018 and SSW 2019, a similar equatorward shift of the maximum wave amplitude at 10 hPa was found: 60-80°N (wave 1), 50-70°N (wave 2), and 50-60°N (wave 3) [24].…”
Section: Introductionmentioning
confidence: 68%
“…The variations in Z1 and Z2 are analyzed during the two winter months, December 2020-January 2021, when a SSW event occurred, and are compared with the three preceding winters of 2018-2020. A zonal wave analysis was carried out along the 50°N latitude circle, passing through the northern Ukraine and northern China, in order to continue the recent studies of mid-latitude SSW manifestations by Wang et al [5,23,34] and Shi et al [24].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations